2014
DOI: 10.7763/ijcea.2014.v5.389
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress of Cadmium-Induced Ovarian Rat Toxicity

Abstract: Abstract-Cadmium (Cd), a common toxic heavy metal, is widely distributed in the environment due to its use in industry. In the industry, Cd is hazardous both by inhalation and ingestion and can cause acute and chronic toxicity. Exposure to Cd had been known to cause damage to organs such as kidney, liver and testis. In this present study Cd was proposed caused an oxidative stress in ovarian rat (Rattus novergicus) cells. Female Rattus novergicus was divided in two groups, one control groups and one case group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Thiols interact and can eventually neutralize hydroxyl radicals and nitric oxide metabolites. 43 Since cadmium induces the formation of free radicals and ROS, 44 it may also be involved in the reduction of serum thiol levels. Additionally, cadmium adverse effects on thiol production may be due to its high affinity for -SH groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thiols interact and can eventually neutralize hydroxyl radicals and nitric oxide metabolites. 43 Since cadmium induces the formation of free radicals and ROS, 44 it may also be involved in the reduction of serum thiol levels. Additionally, cadmium adverse effects on thiol production may be due to its high affinity for -SH groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fundamentally, shreds of evidence have demonstrated the connection of oxidative stress to the central nervous system i.e. pathology of neurological disorders [ 6 ] and the susceptibility of the somatic nervous system (cellular toxicity) to oxidative damage has been conventionally established [ 29 , 30 ]. Nonetheless, the mechanistic applications underlying the nervous system (neuronal toxicity) and cellular system (ovarian-toxicity) using the mammalian model during mixed exposure to environmental toxicants are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fertility disorders associated with abnormal neuronal signaling molecules are speculated to be prevalent among womenfolk in industrialized countries due to consequential exposure to mixed-environmental chemicals. In the past, cancer of the testes, ovaries, prostate, varicoceles, brain, and CNS tumor were identified as the major challenge in human subjects exposed to mixed-metals and toxicants from drinks, foods, and workplaces [ [4] , [5] , [6] ]. Also, childlessness and sterility connected to ovarian dysfunction had been identified in females with a high risk of the psychiatric disorder [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, increased MDA levels observed in blood, ovary and uterus of treated rats in our study indicated to the oxidative damage caused to these tissues due to treatment with the metal mixture. dismutase (SOD) catalyzes the conversion of superoxide radicals to hydrogen peroxide and molecular oxygen, while catalase (CAT) catalyzes the breakdown of toxic hydrogen peroxide (H2O2) to water (H2O2) and oxygen (O2) 39 . Glutathione (GSH) acts as a natural antioxidant and potential reducing agent.…”
Section: Cycle)mentioning
confidence: 99%